Peran Guru Dalam Program Pembinaan Dengan Fiqih Kemasyarakatan - M. Tubi Heryandi (Kependidikan Islam Fakultas Agama Islam, 2019)
The Community Fiqh Development Program is an activity formed because the majority of input from elementary school graduates and many students do not understand religious material, especially about prayer, so this program can be a bridge for students to know in depth knowledge about the correct prayer materials and make it easier for teachers to understand students in terms of performing prayers, because in this program will be taught the material and its practice to students.This research uses a qualitative perspective. The data collection used is by observation, interview and documentation techniques. While the data analysis used is the Miles and Huberman model. The focus of this thesis research is (1), What is an overview of the community fiqh coaching program at MTs Al-Falah, (2), How is the Role of the teacher in the Community Fiqh Guiding Program at Al-Falah MTs.The results of this study are (1), the Community Fiqh Development Program is motivated by the majority of elementary school input graduates, the majority of students do not understand religious material, especially prayer, in its implementation the program is specifically for students of class VII and fostered by the teachers of jurisprudence, SKI teachers, teachers Arabic, and the teacher of the Qur'an Hadith by utilizing the free time of the coach and carried out at school or outside the school, while the material contained in the program is the intention of ablution ', prayer after ablution, intention to bathe large hadast, The intentions of the five maktubah prayers, Prayer Iftitah, fatihahRuku ', i'tidal, prostration, sitting between two prostrations for final tahiyat Prayers, Qunut, supplications for sahwi prostrations, Lafadz adzan and iqomah, Dhikr after the final prayer. So it is mentioned that the program with the program of fostering community fiqh, (2), The role of the teacher in the community fiqh guidance program is as a motivator, as an administrator, as a director, as an assessor, as a supervisor, as a supervisor.